2017
DOI: 10.1097/dcr.0000000000000961
|View full text |Cite
|
Sign up to set email alerts
|

Naples Prognostic Score, Based on Nutritional and Inflammatory Status, is an Independent Predictor of Long-term Outcome in Patients Undergoing Surgery for Colorectal Cancer

Abstract: The Naples prognostic score is a simple tool strongly associated with long-term outcome in patients undergoing surgery for colorectal cancer. See Video Abstract at http://links.lww.com/DCR/A469.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
169
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(180 citation statements)
references
References 30 publications
7
169
2
2
Order By: Relevance
“…The definition of NPS was based on the following four parameters, namely serum albumin, total cholesterol (TC), LMR, and NLR. As previously reported by Gennaro Galizia et al [31], the cut-off values were 4 mg/dL for serum albumin, 180 mg/dL for TC, 2.96 for NLR, and 4.44 for LMR, respectively. Patients with serum albumin, TC or LMR lower than 4 mg/dL, 180 mg/dL, and 4.44 got one point; otherwise, they got zero point.…”
Section: Data Collection and Nps Definitionsupporting
confidence: 69%
See 1 more Smart Citation
“…The definition of NPS was based on the following four parameters, namely serum albumin, total cholesterol (TC), LMR, and NLR. As previously reported by Gennaro Galizia et al [31], the cut-off values were 4 mg/dL for serum albumin, 180 mg/dL for TC, 2.96 for NLR, and 4.44 for LMR, respectively. Patients with serum albumin, TC or LMR lower than 4 mg/dL, 180 mg/dL, and 4.44 got one point; otherwise, they got zero point.…”
Section: Data Collection and Nps Definitionsupporting
confidence: 69%
“…Therefore, multidimensional prognostic evaluating systems which incorporate multiple prognostic factors together may be better than predictors based on single prognostic factor. Recently, a comprehensive prognostic score, the Naples prognostic score (NPS), calculated from serum albumin and total cholesterol concentrations, LMR and NLR, was reported to be a powerful prognostic index for colorectal cancer (CRC) [31]. NPS is a comprehensive scoring system which includes all of the markers that have been predominantly used now.…”
mentioning
confidence: 99%
“…A recent study in patients with cancer has shown that hypoalbuminemia reflects the condition of malnutrition and immunosuppression, and it is at an increased risk of disease severity, tumor progression, and poor prognosis [ 23 ]. Furthermore, serum Alb level has also been widely used in various prognostic indexes, including a prognostic nutritional index (PNI) [ 24 ], a systematic inflammation index (IPI) [ 25 ], and Naples prognostic score (NPS) [ 26 ]. Serum Alb plays important roles in colloid osmotic pressure maintenance, free radical scavenging, and capillary membrane permeability alteration [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the CONUT score on outcomes in patients undergoing surgery for colorectal cancer (CRC) was first reported in 2015 [9]. Since then, it has been further examined, and the efficiency of the CONUT score on outcomes in CRC was demonstrated [10,11]. However, most of these studies had relatively small sample sizes, variance in tumor stage and results that were not uniform.…”
Section: Introductionmentioning
confidence: 99%